الموقف العام للمسلمين من التوغل المغولي في العالم الإسلامي وسقوط بغداد (616 – 656هـ/1219-1258م) - IBRAHIM, SHAABAN FADHIL (Journal of Duhok University, 2023)
When the Mongols invaded the Islamic Orient, especially the Khwarezmian state, in the year (616 AH/1219 AD) the Islamic countries were living in a state of weakness, strife, and disunity, in addition to internal wars and the conflict of Islamic sects among themselves. Two years after that date, the Mongol armies began to penetrate the outskirts of Iraq, the Peninsula, and Asia Minor and continued to attack those countries intermittently until the fall of Baghdad. The countries of Khorasan, Iraq, the Levant, and other Islamic countries were controlled by princes and leaders who, in a state of conflict, preferred their personal interests to the higher interests of the Muslims. The Muslim rulers, in their behavior and dealings with their people or with each other, were afflicted with weakness, tended to selfishness, and monopolized power, and their great leaders followed them, who lost the enthusiasm to confront the enemies, which weakened their morale in confronting the Mongols. None of the Muslim princes and leaders showed any indication of serious interest in the matter or a great danger that began to threaten the Islamic world. Nor was there any evidence that they had established a clear-cut policy to address this dangerous situation. They did not attempt to unite the Muslims in a military alliance against the Mongols. None of the Muslims stood up to the Mongols. The hearts of the people of the cities were filled with fear of them, and no one showed any position that they could possibly confront them.